Using the ADDIE model in development of physics unit convertion application based on Android as learning media - Nurfidah Dwitiyanti; Siti Ayu Kumala; Fita Widiyatun (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
Physics is one of the sciences that studies concepts, laws, formulas, and also real and abstract phenomena. Too many formulas in physics that must be understood by students, make students feel difficult and less enthusiastic in learning physics. One of the material that makes students like to forget is the material about unit conversions where the number of units that need to be remembered are units of length, acceleration, speed, energy and others. To solve this problem, it is necessary to make an application in the android system that can help in unit conversion and easily accessible. The method that will be used in this research is Research and Development (R&D) using the ADDIE Model. Through the ADDIE Model cycle, they are: (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation will be developed in this application. The results of the feasibility test from material experts are based on three aspects of assessment, namely the aspect of language, suitability of concepts and illustrations, which is in the feasible category with a total percentage of eligibility of 79,76%. Meanwhile, based on the results of the media expert feasibility test are based on three aspects of assessment, namely graphics, program processing and usage are in the very feasible category with a total percentage of eligibility of 88,89%.